Contract Academic Librarians in Canada: Stories From a Nation-Wide Survey - McNiff, Lindsay; Carter, Nicole (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2022)
The temporary contract is often framed to Master of Library and Information Studies (MLIS) graduate students as a key gateway into the field of academic librarianship (Lacey 2019), and yet outside of a few important studies and personal reflections, literature on this topic is relatively scarce. This paper reports on the demographics of participant academic librarians who have held temporary contracts in Canada, their career paths, the conditions under which they held contracts, and their experiences of workplace integration and other positive and negative outcomes. Study participants (n=95) have held one or more temporary contracts as an academic librarian in Canada during their career. An online survey was distributed, asking closed and open-ended questions. The data were analyzed using Excel, Qualtrics, NVivo, and manual methods. Participants derived new skills, new networks, satisfaction and confidence from their contract experiences (though sometimes only in retrospect), while others felt excluded, overworked, undervalued, and prevented from making life decisions. And many felt all these things at the same time, meaning that contract academic librarians are caught in a difficult set of competing structural and emotional experiences.